2020
DOI: 10.1007/s00228-020-02862-8
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes and practices of health care professionals towards adverse drug reaction reporting in public sector primary health care facilities in a South African district

Abstract: Purpose Adverse drug reactions (ADRs) have an appreciable impact on patients' health. Little is known however about ADR reporting in ambulatory care environments especially in low-and middle-income countries. Consequently, our aim was to determine knowledge, attitudes and practices (KAP) among health care professionals (HCPs) towards ADR reporting in primary health care (PHC) facilities in South Africa. The findings will be used to direct future activities. Methods Descriptive, cross-sectional design using qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
40
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 74 publications
(88 reference statements)
8
40
1
Order By: Relevance
“…We observed that, compared to medical and surgical specialists, others were more likely to report ADRs, which may perhaps be attributed to greater familiarity of some specialists such as anesthesiologists with ADRs, which constituted the majority of the "others" category in the current study. Similar observations have been reported by some researchers (Bäckström et al, 2000;Dorji et al, 2016;Haines et al, 2020) but not by others (Aziz et al, 2007;Herdeiro et al, 2005). We also observed that female respondents were more likely to have desirable practices compared to male respondents.…”
Section: Discussionsupporting
confidence: 90%
“…We observed that, compared to medical and surgical specialists, others were more likely to report ADRs, which may perhaps be attributed to greater familiarity of some specialists such as anesthesiologists with ADRs, which constituted the majority of the "others" category in the current study. Similar observations have been reported by some researchers (Bäckström et al, 2000;Dorji et al, 2016;Haines et al, 2020) but not by others (Aziz et al, 2007;Herdeiro et al, 2005). We also observed that female respondents were more likely to have desirable practices compared to male respondents.…”
Section: Discussionsupporting
confidence: 90%
“…All Health care professionals (HCPs; doctors, nurses, pharmacists, etc. ), patients and caregivers are the primary source of voluntary ADRs reporting ( Ergün et al, 2019 ; Khan et al, 2020b ; Haines et al, 2020 ). Under-reporting of ADRs continues to be a widespread issue ( Ergün et al, 2019 ; Güner and Ekmekci, 2019 ; Khan et al, 2020a ).…”
Section: Introductionmentioning
confidence: 99%
“…In the study, the results of the first part of the high acuity of critical of ADR reporting system stating from the high score in predictions factors lead to ADR incidences or compare different manufacturing of medications, all rudiments essential were more eighty percepts of responders imitate the excellent of belief of critical of ADR and reporting system and look like the earlier studies. [2,3,6,8,[11][12][13][14][16][17][18][19]21,[38][39][40][41][42] The male gender had more contract than females in some important insights related to the made; maybe the male had more involved in the pharmacy committee than female, which uncovered reasons. The age level factor or level experience will not mark the ADR reporting system's importance.…”
Section: Discussionmentioning
confidence: 99%